The Influence of Reflective Learning Models on Students Historical Empathy Ability - Heri Saputra; Risma M Sinaga; Pargito (MultiTech Publisher, 2023)
History education is often considered boring and students have difficulty understanding its function. However, history lessons can give us an understanding of current and future events. The problem that is often forgotten is actually only related to how we can adapt to learning models that are often less suited to real conditions. This research tested a learning model called reflective learning which was then tested on students, namely Al Kautsar High School students, Bandar Lampung. In this research, researchers used a quasi-experiment, namely one class was the control and the other received treatment in the form of reflective learning model to measure the effect on historical empathy. The research results show that a reflective learning approach can effectively foster historical empathy